Immunoinflammatory responses to febrile lower respiratory infections in infants display uniquely complex/intense transcriptomic profiles - Jones, Anya C.; Anderson, Denise; Galbraith, Sally; Fantino, Emmanuelle; Cardenas, Diana Gutierrez; Read, James F.; Serralha, Michael; Holt, Barbara J.; Strickland, Deborah H.; Sly, Peter D.; Bosco, Anthony; Holt, Patrick G. (Journal of allergy and clinical immunology, 2019)
To the Editor: In a recent birth cohort study published in the Journal of Allergy and Clinical Immunology,1 we observed a high level of variation among children in postnatal development of type 1/type 3 IFN (T1/3IFN) response capacity as measured by in vitro stimulation of PBMC responses to the viral mimic polyI:C. At birth, the mean response capacity (defined here as the number of IFN subtypes expressed) in the cohort investigated was 2.6 ± 3.2 (range, 0-14) of the 17 innate IFN genes tested, and low response capacity was associated with increased risk for persistent wheeze/asthma at age 5 years,1 and for febrile lower respiratory tract infections (fLRTIs) before age 1 year,1 the latter being a recognized risk factor for early onset asthma.2-4 We also showed that the range of T1/3IFNs activated in polyI:C responses in most children expanded markedly between birth and age 4 years.1 As part of earlier studies on this cohort,2,3 we had collected detailed respiratory infection histories on all subjects, and we used these data to test whether the frequency and/or type of infections experienced during infancy influenced this immune maturation process.1 We stratified children into subgroups by infant infection history and compared the breadth of their T1/3IFN responses at age 4 years, and the subgroup who experienced fLRTIs during year 1 stood out as the most immunocompetent by age 4 years on the basis of the number of IFN genes activated via polyI:C (∼4-fold expansion relative to responses at birth).1 This association was higher for fLRTIs than for any other infant infection category including wheezy LRTIs.1 In addition, we have shown that the association between infant LRTI and risk for persistent wheeze/asthma in this cohort is generally stronger for fLRTIs than for other infection categories.1,4,5 These findings suggest that fever may be a marker of respiratory infectious disease events with particularly potent immunomodulatory properties. Notwithstanding this limitation, these preliminary findings collectively are consistent with fever being a marker for LRTIs that provoke maximally intense and complex host immunoinflammatory responses in infants, consistent with the role of this class of infections as strong drivers of both immune maturation1 (viz a viz the “Hygiene Hypothesis”6) and of the initial phase of asthma pathogenesis,3,4 the latter via mediation of airway tissue damage during the crucial early postnatal window period of rapid lung growth and differentiation.7 The implications of these findings are 2-fold. In particular, more detailed characterization of the cellular and molecular networks underlying these febrile responses in infants may provide insight into the molecular mechanisms that drive postnatal immune maturation, and as such provide guidance toward development of immune-enhancing therapeutics for use in infants genetically at “high risk” of asthma/allergy in whom the kinetics of this maturation process are sluggish relative to the rest of the population.8Supplementary data Online Repository textTables E1-E4